2003
DOI: 10.2139/ssrn.476323
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Team Spirit - An Experimental Study

Rupert Sausgruber

Abstract: Team spirit is often suggested as a counter-balancing power to free-riding. Testing for team spirit with field data is difficult, however, due to an inherent identification problem. In this paper we use experimental methods to identify team spirit against potential confounding factors. In a team work task we vary subjects' information about relative team performance while we leave unchanged the structure of explicit incentives. We find that subjects contribute more to their team's project when teams observe ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Hence, increasing the other's incentives to contribute more can be no motive in their experiment. Sausgruber (2005) examines peer e¤ects between teams rather than within teams. He …nds that the average contribution of the other team in the previous period is positively correlated to the contribution of a person to the own team output in the current period.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, increasing the other's incentives to contribute more can be no motive in their experiment. Sausgruber (2005) examines peer e¤ects between teams rather than within teams. He …nds that the average contribution of the other team in the previous period is positively correlated to the contribution of a person to the own team output in the current period.…”
Section: Introductionmentioning
confidence: 99%
“…Sausgruber (2003), who analyzed team spirit in an experiment, also found that subjects contribute significantly more, the higher the average contribution within their team (excluding their own contribution).…”
mentioning
confidence: 95%
“…Individuals want their behavior to be matched with the common behavior (Heinrich 2004). Two recent laboratory studies indicate the strength of "conformity" compared to "reciprocity" (see Bohnet andZeckhauser 2004, andBardsley andSausgruber 2003). On the other hand, the study by Falk, Fischbacher and Gächter (2003) indicates considerable support for reciprocity.…”
Section: Overview Of the Existing Literaturementioning
confidence: 99%